Seroprevalence of Toxoplasma gondii in goats in Hunan province, China - Li, Fen (Parasite, 2016)
Toxoplasma gondii infections are prevalent in animals and humans worldwide. In the present investigation, the seroprevalence of T. gondii in goats was investigated in Hunan province, subtropical China between March 2014 and December 2015. A total of 1,028 serum samples collected from 14 administrative regions of Hunan province were evaluated by the indirect hemagglutination test (IHAT) for the detection of specific antibodies. Antibodies to T. gondii were detected in 124 serum samples (12%). The T. gondii seroprevalence ranged from 1.7% to 19% among different regions in subtropical China, and the differences were statistically significant (p < 0.01). The results of the present survey indicated that T. gondii infection is prevalent in goats in Hunan, which poses a potential risk for human infection with T. gondii in this province.